Medievalism and metal music studies : throwing down the gauntlet - Barratt-Peacock, Ruth; Hagen, Ross (Emerald Publishing Limited, 2019)
Metal music has long nurtured an obsession with visions of the Middle Ages, with countless album covers and lyric sheets populated by Vikings, knights, wizards, and castles. Medievalism and Metal Music Studies: Throwing down the Gauntlet addresses this fascination with all things medieval, exploring how metal musicians and fans find inspiration both in authentically medieval materials and neomedievalist depictions of the period in literature, cinema, and other media. Within metal music, the medieval takes on multiple, and even contradictory meanings, becoming at once a cipher of difference and grotesque alterity while simultaneously being imagined as a simpler, more authentic time, as opposed to the complexities and stresses of modernity. In this fashion, the medieval period becomes both a source for artistic creativity and a vector for countercultural social and political critique. The contributors in this book hail from a wide range of fields including medieval history, music performance, musicology, media studies, and literature, and computer linguistics, bringing a variety of critical perspectives to bear on the topic. Engaging in analyses of cover art, liner notes, lyrics, and musical style, the contributors investigate issues of research methodologies, crucial concerns over identity and nationalism, and the recontextualisation of historical materials, all aimed at critically examining how and why medievalism has permeated heavy metal music and culture. Hearken to our tales!
Includes index.
Keywords: Heavy metal (Music) -- Criticism and interpretation.; Medievalism.; Music, Genres & Styles, Heavy Metal.; Heavy Metal music.; elektronické knihy; electronic books